2014
DOI: 10.1074/jbc.m114.602458
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of (2E)-4-Hydroxy-2-nonenal via ω- and ω-1-Oxidation Stimulated by Ketogenic Diet

Abstract: Background: (2E)-4-hydroxy-2-nonenal (HNE) catabolism and its regulation remain to be fully investigated. Results: New catabolic pathways of HNE via -/-1-oxidation are elucidated and up-regulated in a ketogenic diet. Conclusion: HNE catabolism plays a major role in HNE disposal in certain organs. Significance: This work will further enhance our understanding of the metabolic fate of HNE and the roles of -and -1-oxidations in HNE disposal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…9 ). All together these results indicate an important catabolism of HNE, given by oral or parenteral route, through β-oxidation of HNA and possibly also through ω-oxidation of HNA and further β-oxidation steps originating from the carbon 9 of HNA as recently reported by some authors [23] .…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…9 ). All together these results indicate an important catabolism of HNE, given by oral or parenteral route, through β-oxidation of HNA and possibly also through ω-oxidation of HNA and further β-oxidation steps originating from the carbon 9 of HNA as recently reported by some authors [23] .…”
Section: Resultssupporting
confidence: 83%
“…This metabolite could originate from a β-oxidation step originating from the carbon 9 of HNA, as we observed the “twin compound” still retaining the stable isotope labeling on carbon 1 and 2 (ion at m/z 175), precluding any possibility of β-oxidation step on the carbons 1 and 2 of HNA. The presence of this metabolite accounting for 2% of urinary radioactivity reinforces the HNE disposition pathway evidenced recently by Jin et al [23] .…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Isotope labelling experiments have shown that KD therapy induces cytochrome P450 4A-dependent ω- and ω-1-hydroxylation of reactive lipid species, a novel mechanism that might contribute to the anti-inflammatory properties of KD therapy [42]. …”
Section: Oxidative Stressmentioning
confidence: 99%